Pengaruh Kualitas Produk Harga dan Variasi Produk Terhadap Kepuasan Pelanggan Konveksi Bunda Collection - Tegar Kurniawan; Mariah (UNIVERSITAS KALBIS, 2022)
This study aims find out how much attracting consumers to buy the products offered,is necessary to have high quality product quality, competitive price perceptions, and diverse product variations, provide satisfaction consumers. This research quantitative approach using the SPSS Static 25 program with a sample of 100 respondents who live in Jabodetabek who have purchased Bunda Collection clothing using non-probability sampling and purposive techniques. The results of this study t test shows that product quality an effect customer satisfaction with significance value of 0.000 < 0.5 and a t value of 10.923 > 1.984 that product quality is very important Mother Collection, price variable 4.075 > 1.984 effect and product variation variable 118.004 > 1.984 has significant effect . The benefit of this research for Bunda Collection is as input evaluation material in order to maintain and improve product quality, price, and product variations in order to excel from other competitors